Clínicas del trabajo en Chile : tres experiencias de intervención en una sociedad dañada por la gestión 'managerial' - Patricia Guerrero Morales; Manuel Gárate Chateu; Elisa Ansoleaga Imas; J. Marcelo Balboa Gallardo; José Tomas Saffirio Mezzano; Alejandra Nuñez Carbullancautor; M. Valentina Urrutia Fuenzalida (Universidade do Porto, 2019)
The paper aims at problematizing the process of contemporary work transformations in Chile. Three experiences are described from a clinical point of view (pedagogical, psychosocial and socio-analytical) in different work scenarios. Then, it reflects on the relevance of the clinical approach as a form of intervention, which contributes to the understanding of the workers' subjective processes, in their individual, group and political dimensions.